PEAK GROUND ACCELERATION AT SURFACE AND SPECTRAL ACCELERATION FOR MAKASSAR CITY BASED ON A PROBABILISTIC APPROACH - Bambang Sunardi; Jimmi Nugraha (Jurnal Meteorologi dan Geofisika, 2016)
The December 12, 2010 earthquakes (M 5.9) has drawn attention on the importance of knowledge of peak ground acceleration at surface (PGAM) and spectral acceleration for Makassar City. The PGAM and spectral acceleration play an important role in seismic design regulations. The purpose of this paper is to present the PGAM and spectral acceleration for Makassar City based on a probabilistic approach. The analysis involved determination of peak ground acceleration at bedrock using Probabilistic Seismic Hazard Analysis (PSHA), the average shear wave velocity at 30 m depth (Vs30), and site classification. Results of the analysis showed that the values of PGAM for Makassar City were varied from 0.177 – 0.21 g. Meanwhile, the spectral acceleration values at T = 0.2 and T = 1 second were varied from 0.459 – 0.541 g and 0.277 – 0.369 g respectively. From these results, the values of PGAM and spectral acceleration are relatively higher at Tamalanrea and Biringkanaya districts and relatively lower at Tamalate district in comparison to other districts in Makassar City. This condition is associated with the location of those areas which are relatively closer to the  earthquake source (Walanae fault), and is geologically dominated by stiff soil (SD).Gempa 12 Desember 2010 (M5.9) menarik perhatian kita akan pentingnya pengetahuan tentang percepatan tanah maksimum di permukaan (PGAM) dan spektra percepatan untuk Kota Makassar. PGAM dan spektra percepatan memegang peranan penting dalam peraturan desain gempa. Tujuan dari penelitian ini adalah menentukan PGAM dan percepatan spektra untuk Kota Makassar berdasarkan pendekatan probabilistik. Analisis yang dilakukan meliputi penentuan percepatan tanah maksimum di batuan dasar menggunakan Probabilistic Seismic Hazard Analysis (PSHA), rata-rata kecepatan gelombang geser pada kedalaman 30 m (Vs30), dan klasifikasi site. Hasil analisis menunjukkan bahwa nilai PGAM untuk Kota Makassar bervariasi dari 0.177 – 0.21 g. Sementaraitu, nilai spektra percepatan pada T=0.2 dan T=1 detik berturut-turut bervariasi dari 0.459 – 0.541 g dan 0.277 – 0.369 g. Nilai PGAM dan spektra percepatan relatif lebih tinggi di Kecamatan Tamalanrea dan Biringkanaya serta relatif lebih rendah di Kecamatan Tamalate dibandingkan dengan Kecamatan lainnya di Kota Makassar. Hal tersebut dikarenakan lokasinya yang relatif lebih dekat dengan sumber gempa (patahan Walanae), dan secara geologi di dominasi oleh jenis tanah sedang (SD).